2023
DOI: 10.3390/plants12162968
|View full text |Cite
|
Sign up to set email alerts
|

Allelopathic Activity of the Invasive Plant Polygonum chinense Linn. and Its Allelopathic Substances

Thang Lam Lun,
Shunya Tojo,
Toshiaki Teruya
et al.

Abstract: Polygonum chinense Linn., belonging to the Polygonaceae family, is distributed mostly in northern temperate climates. This species is a high-risk invasive plant and is thought to possess allelopathic potential. This study aimed to isolate and identify the allelopathic substances from P. chinense. Aqueous methanol extracts of P. chinense significantly inhibited the growth of alfalfa and Italian ryegrass seedlings in a species- and concentration-dependent manner. Activity-guided fractionation led to the isolatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Allelochemicals exhibit selectivity and specificity 51 . Prior research has identified that inhibitors of seed germination are predominantly water-soluble organic acids, alcohols, and phenols 52 , 53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allelochemicals exhibit selectivity and specificity 51 . Prior research has identified that inhibitors of seed germination are predominantly water-soluble organic acids, alcohols, and phenols 52 , 53 .…”
Section: Discussionmentioning
confidence: 99%
“…The secondary metabolic substances of T. kanedae encompasses a wide range of allelochemicals and potential allelopathic activity. Allelochemicals exhibit selectivity and specificity 51 . Prior research has identified that inhibitors of seed germination are predominantly water-soluble organic acids, alcohols, and phenols 52,53 .…”
Section: Discussionmentioning
confidence: 99%